Exploring the impact of The Students Assessing Teaching and Learning Program - Signorini, Adriana; Pohan, Cathy (International Journal for Students as Partners, 2019)
The Students Assessing Teaching and Learning (SATAL) Program at the University of California, Merced offers assessment support for faculty and program leads while engaging diverse, cross-program undergraduates in students-as- partners experiences in a work setting. Grounded in the Students as Partners (SaP) principles of respect, responsibility, and reciprocity (Cook-Sather, Bovill, & Felten, 2014), our assessment of the SATAL program reveals benefits for both students and faculty acting as co-creators of teaching and learning. Using the SATAL program as an example, we offer readers a logic model to guide the development of student-faculty-staff partnerships and assess the impact of these programs in a more meaningful and consequential manner. We also provide lessons learned from our evolving SATAL program to support others interested in designing sustainable student assisted assessment partnerships.